Hürthle cell neoplasms of the thyroid: Pathologic outcomes and ultrasonographic analysis. Issue 6 (7th October 2020) - Shin, Timothy J.; Rabbani, Cyrus C.; Murthy, Henna D.; Traylor, Katie; Sim, Michael W.
Abstract: Background: Fine‐needle aspiration (FNA) of thyroid nodules suspicious for Hürthle cell neoplasms (HCN) have uncertain rate of malignancy. We aim to characterize rate and predictors of malignancy at our institution and compare these findings with established literature to help guide management. Methods: Single tertiary‐referral center, retrospective study of 166 adults who underwent hemithyroidectomy or total thyroidectomy following FNA suspicious for HCN from 1998‐2018. Demographic information and surgical histopathologic results were collected. Preoperative ultrasonography was independently scored on the American College of Radiology Thyroid Imaging Reporting and Data System (TI‐RADS) by a board‐certified head and neck radiologist. Results: There were 39 males and 127 females. Overall, 25 (15.1%) patients had carcinoma, with 15 (9%) being Hürthle cell carcinoma (HCC). Men had higher incidence of carcinoma (25.6% v. 11.8%, P = .035), and especially older males. Contralateral carcinoma was seen in 3 of 13 (23.1%) patients that underwent completion thyroidectomy. Patients with carcinoma had larger nodules (average diameter 3.3 cm versus 2.5 cm, respectively, P = .01), but no association with TI‐RADS. Conclusion: Adults with nodules suspicious for HCN have significant risk of malignancy consistent with prior studies. Older males and larger nodule diameter are associated with malignancy in this cohort, but TI‐RADS grade is not. These findings provide a framework for management and counseling for lesions suspicious for HCN. Abstract : A retrospective review of 166 patients who had thyroid nodules suspicious for Hurthle cell neoplasm on FNA and underwent hemi‐ or complete thyroidectomy found that 15.1% of patients had thyroid malignancy. Subgroup analysis suggested that older males and larger nodules are associated with malignancy. TI‐RADS grading was not found to predict malignancy in this cohort.